-5(1-3r)=28+4r

Simple and best practice solution for -5(1-3r)=28+4r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(1-3r)=28+4r equation:


Simplifying
-5(1 + -3r) = 28 + 4r
(1 * -5 + -3r * -5) = 28 + 4r
(-5 + 15r) = 28 + 4r

Solving
-5 + 15r = 28 + 4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-4r' to each side of the equation.
-5 + 15r + -4r = 28 + 4r + -4r

Combine like terms: 15r + -4r = 11r
-5 + 11r = 28 + 4r + -4r

Combine like terms: 4r + -4r = 0
-5 + 11r = 28 + 0
-5 + 11r = 28

Add '5' to each side of the equation.
-5 + 5 + 11r = 28 + 5

Combine like terms: -5 + 5 = 0
0 + 11r = 28 + 5
11r = 28 + 5

Combine like terms: 28 + 5 = 33
11r = 33

Divide each side by '11'.
r = 3

Simplifying
r = 3

See similar equations:

| 5+2x=4x-13 | | 4n+6+-2n=2(n+3) | | 5x+9*0=45 | | 1+6.33z=-2.5 | | 0.062=-0.06m-0.01 | | x^2-20=-125 | | 85=-5(2r-7) | | 4(3-2n)=n+66 | | -4m-7(6-2m)=22 | | 5*0+9y=45 | | .33x=1.33 | | 8y-12-4y+9=0 | | 8y+7=4y-29 | | 9(4-2x)=3(2-6x) | | 15x^2-50x=0 | | 5x-4x=-6+3 | | 0.60x+0.30(70)=0.30(148) | | h/3+h/6=1 | | 7y-20=-2y-47 | | 9=-4.3 | | -6+6n=6(10-10n) | | 3m+8=m+18 | | 36p+4j=33 | | 3x^4+21x^3-36x^2+3=0 | | 2g+4h=47 | | 2g*4h=47 | | 3y-11=5y-35 | | 4b=9(b+5) | | -6y+17=-9y-7 | | 7b-10+1+10b=60 | | -3k+14=-4+3k | | 3X^2-3X+10=04 |

Equations solver categories